L’intégration verticale dans l’industrie minière - Bernard, Jean-Thomas (L'Actualité économique)

(untitled) (HEC Montréal, 1977)
AbstractVertical integration occurs when a transaction between two consecutive stages of production is carried through an internal organisation rather than the market. For most mineral products that are found in Canada, we can observe a fairly high degree of vertical integration from exploration up to refining. The purpose of this paper is to review the various approaches that have been used to study vertical integration in economic analysis and to evaluate their applicability to the Canadian mining sector. Thus far economists have approched vertical integration from three different stand points: first, the efficiency of interval organisation relative to the market in dealing with uncertainty under certain circumstances; second, the capacity to extend market power through vertical integration, and third, vertical integration can arise as an adjustment to some institutional constraints resulting mostly from government interventions. Although the efficiency and the monopolistic argument have contributed to vertical integration in the Canadian mining sector, government intervention in the form of special tax rules have also played a major role.